NEST3D printed bone-mimicking scaffolds: assessment of the effect of geometrical design on stiffness and angiogenic potential - Doyle, Stephanie E.; Pannella, Micaela; Onofrillo, Carmine; Bellotti, Chiara; Di Bella, Claudia; O’Connell, Cathal D.; Pirogova, Elena; Lucarelli, Enrico; Duchi, Serena (Frontiers in Cell and Developmental Biology, 2024)
Tissue engineered implants for bone regeneration require consideration regarding their mineralization and vascularization capacity. Different geometries, such as biomimetic designs and lattices, can influence the mechanical properties and the vascularization capacity of bone mimicking implants. Negative Embodied Sacrificial Template 3D printing (NEST3D) is a versatile technique across a wide range of materials that enables the production of bone mimicking scaffolds. In this study, different scaffold motifs (Logpile, Voronoi and Trabecular Bone) were fabricated via NEST3D printing in polycaprolactone, to determine the effect of geometrical design on stiffness (10.44 ± 6.71, 12.61 ± 5.71, 25.93 ± 4.16 MPa respectively) and vascularization. The same designs, in a polycaprolactone scaffold-only, or when combined with gelatin methacrylolyl, were then assessed for their ability to allow infiltration of blood vessels in a chick chorioallantoic membrane (CAM) assay, a cost-effective and time efficient in ovo assay to assess vascularisation. Our findings showed that gelatin methacrylolyl alone did not allow new chorioallantoic membrane tissue or blood vessels to infiltrate within its structure. However, polycaprolactone on its own or when combined with gelatin methacrylolyl allowed tissue and vessel infiltration in all scaffold designs. The Trabecular Bone design showed the greatest mineralised matrix production over the three designs tested. This reinforces our hypothesis that both biomaterial choice and scaffold motifs are crucial components for a bone mimicking scaffold.